(untitled) (Bombay Hospital Journal, 2026)
Introduction: A comprehensive general physical and systemic examination is fundamental in evaluating patients with neurological disorders. It helps not only in localizing neurological dysfunction but also in identifying systemic conditions, such as diabetes, hypertension, and infections, that may contribute to or mimic neurological symptoms. A thorough examination is crucial for accurate diagnosis and effective management. Key components of the physical examination: This includes an assessment of the patient’s general appearance, vital signs, head and neck, cardiovascular, respiratory, musculoskeletal, gastrointestinal and dermatological systems. Each of these aspects can reveal significant clinical findings, ranging from facial expressions and posture indicative of specific neurological disorders to skin manifestations and cardiovascular irregularities that provide clues for underlying conditions. The systemic examination’s depth depends on the patient’s history, yet a complete assessment is crucial for uncovering unexpected findings and ensuring accurate diagnosis and management of neurological conditions. Conclusion: By incorporating both targeted neurological and broader systemic assessments, this approach facilitates the holistic evaluation of patients helping in optimizing treatment strategies for neurological disorders